L’informalità del cambiamento urbano. Pratiche e progettualità dell’abitare nel quartiere San Berillo di Catania - Lo Re, Vincenzo (Cambio. Rivista sulle Trasformazioni Sociali, 2018)
This ethnographic research focuses on the informal activities that take place in the streets of the San Berillo neighbourhood in the historical centre of the city of Catania, highlighting the stories and meanings that are linked to these uses as a production of transformation and planning. Urban regeneration is an important resource to improve the urban quality, but this process can be produce marginalization and displacement process in the city context. Rethinking the city by expanding the elements of reference, it means recognizing in the urban practices, in the meanings from the bottom and in the symbolic dimension, interpretive categories endowed with planning. Urban practices play a decisive role in the construction of the city. Although they are often more easily associated with abusivism, they constitute the fundamental and prevailing modalities of urban development. The city is not given only by a constructive process of physical space but is the result of adaptation and appropriation of spaces to redefine their uses.